2019
DOI: 10.1073/pnas.1820210116
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling ancestry, kinship, and violence in a Late Neolithic mass grave

Abstract: The third millennium BCE was a period of major cultural and demographic changes in Europe that signaled the beginning of the Bronze Age. People from the Pontic steppe expanded westward, leading to the formation of the Corded Ware complex and transforming the genetic landscape of Europe. At the time, the Globular Amphora culture (3300–2700 BCE) existed over large parts of Central and Eastern Europe, but little is known about their interaction with neighboring Corded Ware groups and steppe societies. Here we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
145
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(171 citation statements)
references
References 45 publications
11
145
0
6
Order By: Relevance
“…We found a rather high number of mitochondrial lineages (14 haplotypes in 24 individuals). High mtDNA diversity in combination with archaeological and isotope evidence can indicate female exogamy (21,40,41). Given the absence of genetic substructure and the fact that both Y-chromosomal and mitochondrial diversity is moderateto-high at Mokrin, the most parsimonious explanation is that this cemetery served a single, large, and contiguous population.…”
Section: Phenotypic Markersmentioning
confidence: 99%
“…We found a rather high number of mitochondrial lineages (14 haplotypes in 24 individuals). High mtDNA diversity in combination with archaeological and isotope evidence can indicate female exogamy (21,40,41). Given the absence of genetic substructure and the fact that both Y-chromosomal and mitochondrial diversity is moderateto-high at Mokrin, the most parsimonious explanation is that this cemetery served a single, large, and contiguous population.…”
Section: Phenotypic Markersmentioning
confidence: 99%
“…The analysis of a Late Neolithic mass grave from Poland, associated with the Globular Amphora Culture, demonstrated that the 15 buried individuals belonged to the same extended family. The relative position of the bodies was in accordance with kin relationship, revealing that, after a violent death, someone who knew these people, took care of their burial (Schroeder et al, 2019).…”
Section: Ngs Methodsmentioning
confidence: 79%
“…This means that in order to better understand the processes connected to human mobility, we should not only look at the overall European scale, but rather we have to treat every regional and local situation as a historical case by itself, in which some overall factors might come to play, but which will still show specific characteristics. So in order to better understand the overall situation, we need more regional and local case studies combining archaeological and molecular biological data, like the one from Knipper et al (2017), Mittnik et al (2019) or Schroeder et al (2019). And also, we should pay more attention to the excellent archaeological work that has been, and is currently being carried in several regions for the third millen nium BC (Larsson 2009; Beckerman 2015; Iversen 2015; Suter 2017; Großmann 2016; Schultrich 2019; Kleijne 2019 just to name a few).…”
Section: Resultsmentioning
confidence: 99%
“…To bring these nuances to the fore goes beyond a short paper, but the large body of archaeological work on third millennium local and regional contexts referred to here demonstrates that the material for such an endeavour is already available. It will have to be combined and better integrated with molecular biological studies, which now thankfully increasingly move towards local scale levels (Veeramah 2018;Schroeder et al 2019).…”
Section: Alternative Approaches To the Archaeology Of The Third Millementioning
confidence: 99%